PENERAPAN DIVERSI TERHADAP ANAK PELAKU TINDAK PIDANA PENCURIAN DIWILAYAH HUKUM POLSEK SLEMAN - sudarno sudarno; Suryawan Raharjo (Kajian Hasil Penelitian Hukum, 2022)
With the development of the era of the population in the Sleman sub-district, Sleman Regency, Yogyakarta Special Region, currently experiencing changes in the way of life in society and an increasingly growing economy and the number of immigrants from other regions who are economically capable who live in the Sleman Regency area so that it will affect the lifestyle of children. -children in the mix. As is happening now, there are public reports to the Sleman Sector police for cases of theft and abuse committed by children to find out the application of diversion to children who are perpetrators of the crime of theft by Sleman Police Investigators. The research method is a descriptive empirical juridical approach.The application of diversion is carried out by Sleman Police Investigators in overcoming the problem of diversion in cases of children in the crime of theft at the Sleman Police, which refers to Law Number: 11 of 2012 concerning the Juvenile Criminal Justice System. The implementation of diversion at the Sleman Police has two obstacles, namely; Internal Barriers, and External Barriers and Efforts made by Sleman Police Investigators and Youth Social Rehabilitation and Protection Center (BPRSR) Yogyakarta Social Service to create justice for Sleman Police investigators seek a diversion process between by: Bringing the litigants together for settlement through the diversion process, invites from the Correctional Center, SOCIAL Activists, legal counsel for child offenders and parents of child offenders to accompany, Investigators immediately request the determination of the results of the diversion to the Court.